β-Adrenergic signaling in rat heart is similarly affected by continuous and intermittent normobaric hypoxia - Hahnova, Klara; Kasparova, Dita; Zurmanova, Jitka; Neckar, Jan; Kolar, Frantisek; Novotny, Jiri (General physiology and biophysics, 2016)
Chronic hypoxia may produce a cardioprotective phenotype characterized by increased resistance to ischemia-reperfusion injury. Nevertheless, the molecular basis of cardioprotective effects of hypoxia is still not quite clear. The present study investigated the consequences of a 3-week adaptation to cardioprotective (CNH, continuous normobaric hypoxia) and nonprotective (INH, intermittent normobaric hypoxia; 23 h/day hypoxia followed by 1 h/day reoxygenation) regimen of hypoxia on β-adrenergic signaling in the rat myocardium. Both regimens of hypoxia lowered body weight and led to marked right ventricular (RV) hypertrophy, which was accompanied by 25% loss of β1-adrenergic receptors (β1-ARs) in the RV. No significant changes were found in β-ARs in left ventricular (LV) preparations from animals adapted to hypoxia. Although adenylyl cyclase (AC) activity stimulated through the G proteins was decreased in the RV and increased in the LV after exposure to hypoxia, there were no significant changes in the expression of the dominant myocardial AC 5/6 isoforms and the stimulatory G proteins. These data suggest that chronic normobaric hypoxia may strongly affect myocardial β-adrenergic signaling but adaptation to cardioprotective and nonprotective regimens of hypoxia does not cause notably diverse changes.
Keywords: Receptors, Adrenergic, beta; beta-adrenergní receptory; Male; Oxygen; Rats, Wistar; Adaptation, Physiological; signální transdukce; Hypoxia; Myocardium; mužské pohlaví; potkani Wistar; fyziologická adaptace; Signal Transduction; krysa rodu Rattus; Animals; kyslík; zvířata; Rats; hypoxie; myokard